Mau MC24 : Bruce Mau's 24 principles for designing massive change in your life and work - Mau, Bruce, 1959-; Ward, Jon, ....- (London ; New York, NY : Phaidon Press Limited, 2020)
Bruce Mau has long applied the power of design to transforming the world. Developed over the past three decades, this remarkable book is organized by 24 values that are at the core of Mau's philosophy. MC24 features essays, observations, project documentation, and design work by Mau and other high-profile architects, designers, artists, scientists, environmentalists, and thinkers of our time. Practical, playful, and critical, it equips readers with a tool kit and empowers them to make an impact and engender change on all scales.
Includes bibliographical references and index.
Keywords: Design; Industrial design